Energy consumption synchronization between Europe, United States and Japan: A spectral analysis assessment. (September 2017) - Dima, Bogdan; Dima, Ştefana Maria
Abstract: This paper aims to advance a model able to explain the synchronization tendency in energy consumption, under the impact of international technology transfers. The key argument is related to the differences in energy consumption efficiency of local and foreign technologies. One direct testable consequence of the model is that there might be a certain correlation between the energy consumption between countries and/or economic areas where a free movement of capital goods and technologies takes place. Hence, it is further tested, in the framework of a multivariate spectrum analysis, the case of energy consumption synchronization between Europe and, respectively, United States and Japan for a time span between 1981 and 2011 based on the data provided by U.S. Energy Information Administration. There are evidences of a leading behavior of energy consumption in United States and Japan in respect to Europe as well as of short-run phase delays of 2 up to 5 months. Highlights: We propose a model to explain the synchronization in energy consumption. The driven factors are related to international technology transfers. We test the synchronization in energy consumption based on a spectrum analysis. There is a leading in energy consumption from United States and Japan. There are phase delays up to 5 months between Europe and its main partners.